A new species of Camellocossus Yakovlev, 2011 (Lepidoptera: Cossidae) from Southern Oman - Yakovlev, Roman V.; Saldaitis, Aidas; Rimsaite, Jolanta; Ivinskis, Povilas (Zootaxa, 2015)
The genus Camellocossus Yakovlev, 2011 (Lepidoptera: Cossidae) was established for Cossus abyssinica (Hampson 1910) by Yakovlev (2011). Camellocossus is close to Mahommedella Yakovlev, 2011 (type species—Catopta rungsi (Daniel & Witt 1974), distributed in Western part of Sahara) but differs from it by having the following characters: 1) male antennae have much shorter rami 2) a straight phallus, 3) juxta with acute-angled upwardly divergent lateral processes. Currently, three species are included in the genus Camellocossus (Yakovlev 2011): C. abyssinica (Hampson, 1910), C. henleyi (Warren & Rothschild 1905) and C. osmanya Yakovlev (2011). Members of the genus are spread throughout Northern Africa (Algeria, Egypt, Ethiopia, Mauritania, Morocco, Somalia, Sudan and Yemen). The host plants – Vachellia nilotica and V. tortilis var. raddiana (de Joannis 1909; Rungs 1972) are known for C. henleyi. During a study of Arabian Lepidoptera by Jurgen Krüger and Aidas Saldaitis a new species of the genus Camellocossus was discovered and is described below. All specimens were collected using light traps. The genitalia slides were examined with the use of a Zeiss Stemi 2000 C microscope and the images were taken with an Olympus XC 50 camera.